(t, n) Threshold Quantum State Sharing Scheme Based on Linear Equations and Unitary Operation - Cao Hao; Ma Wenping (IEEE Photonics Journal)
Quantum state sharing (QSTS) plays an important role in transporting, managing, and distributing keys. In this paper, by adopting the linear equation instead of using the Lagrange interpolation, a new idea of constructing (t, n) threshold quantum state sharing scheme is proposed. The best innovation is that a new tool in constructing (t, n) threshold structure is proposed. In this scheme, the dealer who possesses a sequence of one-particle unknown quantum states intends to share it with n participants and authorizes t out of them cooperate to reconstruct the sequence. First, the equations decided by the private key of dealer are constructed. Second, the dealer distributes the private keys of n participants by using the solutions to the equations just mentioned. Finally, the dealer encodes the sequence through a unitary operation, and any t out of the n participants recover the initial quantum state sequence through the unitary operations decided by the solutions to the linear equations. Compared to the existing schemes, the proposed scheme is easily realized in physical experiment, and its successful probability is 100% theoretically.